Ventricular Arrhythmias and Myocardial Infarction: Electrophysiological and Neuroimmune Mechanisms - Meng Zheng; Zhen Zhou; Ke-Qiong Deng; Hanyu Zhang; Ziyue Zeng; Yongkang Zhang; Bo He; Huanhuan Cai; Zhibing Lu (Biomedicines)
Ventricular arrhythmias (VAs) after myocardial infarction (MI) are still one of the most important causes of cardiovascular death, though patients receive timely vascular recanalization and drug treatment. And it requires further exploring the mechanism and new therapeutics of VAs induced by MI. Here, we review the electrophysiological and neuroimmune mechanisms of VAs induced by MI. Immune cells are regulated by combining with neuroendocrine molecules released by the sympathetic nervous system (SNS), and, in turn, they modulate SNS both at the paraventricular nucleus of the hypothalamus and stellate ganglion by releasing cytokines or chemokines. In addition, ‘life essentials’ such as sleep, physiological health, and exercise can also influence cardiovascular health through neuroimmune mechanisms. Those factors and mechanisms provide us with new perspectives for understanding the occurrence and maintenance of VAs after MI. Exploring the crosstalk between electrophysiology and neuroimmunology will contribute to finding new therapeutics for VAs after MI.